TEKNOLOGI INFORMASI DAN PERUBAHAN SOSIAL: STUDI KEHIDUPAN MASYARAKAT DESA SETONO - Ahmada Ghina Ghoniah; Syamsul Bakhri (Journal SOSIOLOGI, 2024)
The advancement of information technology has brought significant impacts on community life, including in Setono Village. The purpose of this study is to understand how technology influences social interactions within the community, to identify its positive and negative effects, and to examine how people adapt to these social changes. A qualitative descriptive approach was employed through interviews and direct observations. The findings reveal that information technology not only facilitates access to information and communication but also transforms social traditions such as gotong royong (mutual cooperation), which has gradually declined. This phenomenon is analyzed using symbolic interactionism and social conflict theories. Technological change within society presents challenges such as social inequality and the diminishing sense of solidarity; however, it also offers opportunities for building social networks and enhancing community participation through digital media. This study highlights the importance of information technology in addressing its own impacts, including fostering wise and ethical technology use, preventing misuse, and maintaining a balance between modernity and tradition. Therefore, technology can serve as an instrument of empowerment without undermining fundamental social values.